Characterization of Arabidopsis thaliana thylakoid lumen 7.6 protein functions in photosystem II assembly - Pan Ren; Ruizi Li; Kai Chen; Chenchen Zheng; Zitian Li; Tao Wang; Cong Ma; Bingyao Li; Xu Wang; Fei Sun; Tengyue Zhang; Yike Xie; et al. (Communications Biology)
Abstract Cyclophilin 38 (CYP38) plays a crucial role in the assembly and stability of photosystem II (PSII), but its molecular mechanism remains unclear. In this study, we identified thylakoid lumen protein 7.6 (TLP7.6) as an in vivo interactor of CYP38. Under normal growth conditions, the tlp7.6 single mutant exhibited no significant phenotypic differences compared to wild-type Col-0. However, the cyp38-2/tlp7.6-1 double mutant displayed severe developmental defects, including stunted growth, delayed flowering, yellowish leaf, short primary roots, abnormal chloroplast ultrastructure, and reduced biomass, which were more pronounced than those in either the tlp7.6 or cyp38-2 single mutant. Photosynthetic analysis revealed that PSII capacities in cyp38-2/tlp7.6-1 and cyp38-2 mutants were significantly reduced, consistent with their slow-growth phenotype. Blue native PAGE analysis demonstrated a substantial reduction in PSII supercomplexes and light-harvesting complex II (LHCII) in cyp38-2/tlp7.6-1, while PSII monomer (PSII-M) were significantly increased. Immunoblotting and two-dimensional gel electrophoresis further confirmed decreased levels of key components of PSII, PSI, and ATPase subunits in the double mutant. Altogether, these results highlight the role of TLP7.6 as an assistive factor in CYP38-mediated PSII assembly, and provide insights into thylakoid lumen protein function in photosynthesis.